Cracking the Black Box: Capturing the Role of Expectation States in Status Processes. (March 2020) - Kalkhoff, Will; Melamed, David; Pollock, Josh; Miller, Brennan; Overton, Jon; Pfeiffer, Matthew
A fundamental task for sociology is to uncover the mechanisms that produce and reproduce social inequalities. While status characteristics theory is the favored account of how social status contributes independently to the maintenance of inequality, it hinges on an unobserved construct, expectation states, in the middle of the causal chain between status and behavior. Efforts to test the mediation mechanism have been complicated by the implicit, often unconscious, nature of status expectations. To solve this "black box" problem, we offer a new conceptualization and research approach that capitalizes on the accuracy and precision of neurological measurement to shed new light on the biasing role of expectations in the status–behavior relationship. Results from an experimental study provide a unique illustration of ways in which social status is inscribed in the brain and how, in turn, these inscriptions are related to behavioral inequalities that emerge during interaction.